Equações de Painlevé mistas e modelo PIII-PV simétrico - Ruy, Danilo Virges [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This thesis studies the connection among integrable models and Painlev'e equations. We begin by extending the modiﬁed truncation approach in order to ﬁnd B¨acklund transformations for the mKdV-Liouville hierarchy and its self-similarity reduction. With this method, we solve Kudryashov's conjecture partially. Then we study the extended mixed AKNS-Lund-Regge model and show this model can be reduced to PIV and PV equation for particular values of the parameters. We also construct the symmetric PIII-PV model in order to unify some cases of the PIII equation with the PV equation. After, we search for canonical constraints for reduce the 4-bose model to the symmetric PIII-PV model. For ﬁnd the correct constraints, we construct the method of ansatz of constraints. In addition, we show a method for ﬁnding solutions for diﬀerential equations inD dimensions in the addendum. We also apply this method for the 'lâmbda'fi'POT.4 model

Esta tese aborda a conexão entre modelos integráveis e as equações de Painlevé. Começamos estendendo o método do truncamento modiﬁcado aﬁm de encontrar transformações de Bäcklund para a hierarquia mKdV-Liouville e sua redução por auto-similaridade. Com este método, resolvemos parcialmente a conjectura de Kudryashov. Em seguida, estudamos o modelo misto AKNS-Lund-Regge estendido e mostramos que este modelo pode ser reduzido às equações PIV e PV para valores particulares dos parâmetros. Nós também construimos o modelo PIII-PV simétrico aﬁm de uniﬁcar alguns casos da equação PIII com a equação PV. Posteriormente, buscamos os vínculos canônicos apropriados que reduzem o modelo 4-bósons ao modelo PIII-PV simétrico. Para isso, elaboramos o método do ansatz de vínculos. Complementarmente, apresentamos um método para encontrar soluções de equações diferenciais em D dimensões no adendo e aplicamos ao modelo 'lâmbda'fi'POT.4
Keywords: Painlevé, Equações de; Teoria de campos; Backlund, Transformações de; Dirac, Equações de